Randomized Control Trial of Peer-Delivered, Modified Directly Observed Therapy for HAART in Mozambique - Pearson, Cynthia R. (2007)
OBJECTIVE: To assess the efficacy of a peer-delivered intervention to promote short-term (6-month) and long-term (12-month) adherence to HAART in a Mozambican clinic population. DESIGN: A 2-arm randomized controlled trial was conducted between October 2004 and June 2006. PARTICIPANTS: Of 350 men and women (≥18 years) initiating HAART, 53.7% were female, and 97% were on 1 fixed-dose combination pill twice a day. INTERVENTION: Participants were randomly assigned to receive 6 weeks (Monday through Friday; 30 daily visits) of peer-delivered, modified directly observed therapy (mDOT) or standard care. Peers provided education about treatment and adherence and sought to identify and mitigate adherence barriers. OUTCOME: Participants' self-reported medication adherence was assessed 6 months and 12 months after starting HAART. Adherence was defined as the proportion of prescribed doses taken over the previous 7 days. Statistical analyses were performed using intention-to-treat (missing = failure). RESULTS: Intervention participants, compared to those in standard care, showed significantly higher mean medication adherence at 6 months (92.7% vs. 84.9%, difference 7.8, 95% confidence interval [CI]: 0.0.02, 13.0) and 12 months (94.4% vs. 87.7%, difference 6.8, 95% CI: 0.9, 12.9). There were no between-arm differences in chart-abstracted CD4 counts. CONCLUSIONS: A peer-delivered mDOT program may be an effective strategy to promote long-term adherence among persons initiating HAART in resource-poor settings.